2023
DOI: 10.1002/bmc.5662
|View full text |Cite
|
Sign up to set email alerts
|

Ellagic acid from pomegranate peel: Consecutive countercurrent chromatographic separation and antioxidant effect

Abstract: Ellagic acid is one of the most representative natural antioxidants, and is rich in pomegranate peel. In this study, a consecutive countercurrent chromatographic (CCC) separation method was established to improve the preparative efficiency of ellagic acid from pomegranate peel. By optimizing the solvent system, sample size and flow rate, 280 mg of ellagic acid was obtained from 5 g of crude sample from pomegranate peel by CCC after six consecutive injections. Moreover, the values of EC50 for ellagic acid in sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…It is first hydrolyzed before it can be absorbed and utilized by the human body 14 . Ellagic acid mainly has anti-inflammatory, antibacterial, antiviral, and anti-tumor pharmacological effects, and is a natural inhibitor of NF-κB 15 22 . Studies have shown that ellagic acid can relieve diarrhea, so it has a very high potential efficacy for anti-RV 23 .…”
Section: Introductionmentioning
confidence: 99%
“…It is first hydrolyzed before it can be absorbed and utilized by the human body 14 . Ellagic acid mainly has anti-inflammatory, antibacterial, antiviral, and anti-tumor pharmacological effects, and is a natural inhibitor of NF-κB 15 22 . Studies have shown that ellagic acid can relieve diarrhea, so it has a very high potential efficacy for anti-RV 23 .…”
Section: Introductionmentioning
confidence: 99%